(3CSS GdLZQGajI GdGbJUGOjI (B/s - (3gGQhf, Ydj GMeOs ((3GdbGgQI(B: s (3OGQ GdacQ GdYQHj(B, s, 2006)
(3eONd Gdi GdLZQGajI GdGbJUGOjI h JfGhd GdehGQO GdGbJUGOjI h GdGfJGL GdGbJUGOj h cPG GdSjGMI h GdehGQO GdRQGYjI h GdeMGUjd GdRQGYjI GdZPGFjI h eMGUjd GdNVQ h GdaGcgI h eMGUjd GdGdjGa h eMGUjd PGJ WHjYI NGUI h GdGfJGL GdMjhGfj h GdehGQO GdeGFjI h eTcdI GdZPGA aj GdYGde h cPG GdehGQO GdZGHjI h GdGfJGL GdeYOfj h cPG GdUfGYI h Gdfbd h GdJLGQI (B.s
(3eQGLY U(B.667s
Keywords: (3GdLZQGajG GdGbJUGOjIs